(untitled) (Journal of Atomic and Molecular Sciences, 2019)
PRODAN derivatives would be a potential probe molecules. The hydrogen bond effects in PRODAN derivatives on excited state in methanol solvent have some significance to explain their dynamic experiments. In this paper, we have presented a theoretical investigation into the influence of hydrogen bonding on the structural and spectral properties of PRODAN derivative (1a) and methanol complexes using time dependent density functional theory. The focused work is the structures and vibrational spectra of PRODAN derivative (1a) hydrogen bonding compounds in methanol solvent. It was observed that the distances of hydrogen bonding between derivative and methanol molecule in complexes shortened in the S_1 state. The results suggested that the behavior and effect of hydrogen bonds increased in the excited proceed. In addition, the IR vibrational spectra of PRODAN-1a-MeOH complex occurred shift in the S_1 state. As a consequence, the hydrogen bonding of PRODAN derivative (1a) could play a role in the geometries and electronic spectra in excited state.